Cognitive and affective empathy in binge drinking adolescents: Does empathy moderate the effect of self-efficacy in resisting peer pressure to drink?. (February 2019) - Laghi, Fiorenzo; Bianchi, Dora; Pompili, Sara; Lonigro, Antonia; Baiocco, Roberto
Abstract: Binge drinking during adolescence is influenced by peer pressure and group norms as risk factors. Conversely, drinking refusal self-efficacy is a protective factor. Thus, adolescents with impaired social skills could be more vulnerable to binge drinking. However, there is still little research on impaired social abilities, such as low empathy, in adolescent binge drinkers. This study aimed to investigate the moderating roles of empathic concerns and perspective-taking in the relationship between self-efficacy in resisting peer pressure to drink (SRPPD) and binge drinking. Participants were 188 Italian adolescents ( M ag e  = 16.93, SD age  = 0.76; age-range: 15–19). Self-report instruments were administered. Binge drinking was evaluated with an open response item according to the clinical definition of symptoms; SRPPD was assessed with an item from the Perceived Self-Efficacy scale; empathic concerns and perspective-taking were measured with the Interpersonal Reactivity Index scale. A moderation regression analysis was run. Results showed that binge drinking is positively predicted by age, and negatively predicted by SRPPD and empathic concerns. Only perspective-taking proved to be a moderator in the relationship between SRPPD and binge drinking. In the presence of low perspective-taking, adolescents with low SRPPD reported more binge drinking than adolescents with high SRPPD. Conversely, for adolescents with high levels of perspective-taking, low SRPPD did not predict binge drinking. Our results shed light on patterns of cognitive and affective empathy in binge drinking adolescents, providing relevant implications for research and prevention for at-risk teenagers. Highlights: The study aims at investigating the role of empathy in binge drinking adolescents. Only cognitive empathy moderate the effect of self-efficacy in resisting peer pressure at drinking. Our results shed light on patterns of cognitive and affective empathy in binge drinking.